Gut microbiome and metabolome in a non-human primate model of chronic excessive alcohol drinking - Daria Piacentino (Nature Publishing Group, 2021)
Abstract A relationship between the gut microbiome and alcohol use disorder has been suggested. Excessive alcohol use produces changes in the fecal microbiome and metabolome in both rodents and humans. Yet, these changes can be observed only in a subgroup of the studied populations, and reversal does not always occur after abstinence. We aimed to analyze fecal microbial composition and function in a translationally relevant baboon model of chronic heavy drinking that also meets binge criteria (drinking too much, too fast, and too often), i.e., alcohol ~1 g/kg and blood alcohol levels (BALs) ≥ 0.08 g/dL in a 2-hour period, daily, for years. We compared three groups of male baboons (Papio anubis): L = Long-term alcohol drinking group (12.1 years); S = Short-term alcohol drinking group (2.7 years); and C = Control group, drinking a non-alcoholic reinforcer (Tang®) (8.2 years). Fecal collection took place during 3 days of Drinking (D), followed by a short period (3 days) of Abstinence (A). Fecal microbial alpha- and beta-diversity were significantly lower in L vs. S and C (p’s < 0.05). Members of the commensal families Lachnospiraceae and Prevotellaceae showed a relative decrease, whereas the opportunistic pathogen Streptococcus genus showed a relative increase in L vs. S and C (p’s < 0.05). Microbiota-related metabolites of aromatic amino acids, tricarboxylic acid cycle, and pentose increased in L vs. S and C (FDR-corrected p < 0.01), with the latter two suggesting high energy metabolism and enhanced glycolysis in the gut lumen in response to alcohol. Consistent with the long-term alcohol exposure, mucosal damage and oxidative stress markers (N-acetylated amino acids, 2-hydroxybutyrate, and metabolites of the methionine cycle) increased in L vs. S and C (FDR-corrected p < 0.01). Overall, S showed few differences vs. C, possibly due to the long-term, chronic alcohol exposure needed to alter the normal gut microbiota. In the three groups, the fecal microbiome barely differed between conditions D and A, whereas the metabolome shifted in the transition from condition D to A. In conclusion, changes in the fecal microbiome and metabolome occur after significant long-term excessive drinking and are only partially affected by acute forced abstinence from alcohol. These results provide novel information on the relationship between the fecal microbiome and metabolome in a controlled experimental setting and using a unique non-human primate model of chronic excessive alcohol drinking.